Specialized Training of Wrestlers at the Stage of Initial Sports Training - Bayturaev Yerlan Isakovich (Zien Journals, 2022)
In this work, we studied the effectiveness of the use of non-traditional training methods for young sambists from the initial training period
Keywords: physical training; technical training; tactical training; methodology